Fundamental Approaches to Software Engineering: 21st International Conference, FASE 2018, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018, Thessaloniki, Greece, April 14-20, 2018, Proceedings - Russo, Alessandra; Schürr, Andy (Theoretical Computer Science and General Issues, 2018)
computer software maintenance; computer software selection and evaluation; formal logic; formal methods; formal specification; programming languages; semantics; software engineering; specifications; verification